Evaluation of ilizarov in infected non-union of long bones - B.S. Brar; HKS Chawla; Ashish Garg; Nishant Pawar (GMC Patiala Journal of Research and Medical Education, 2019)
nfected non-union is a common concern with fractures. Co-existing problems of bone loss, deformities, limb length inequality usually exist. Despite the advancement in treatment methods, infected non-union still remains a challenge for the surgeon as well as the patient. The aim of this study is to evaluate the efficacy of Ilizarov ring fixator in the management of infected non-union of long bones. Method: A group of 30 patients with mean age 36.26 years (18-60) were included in the study. All patients were managed with the described ring fixator. Result: Average shortening was 2.95 cm. Resolution of infection and bony union occurred in all the cases.Mean duration of treatment was 13.7 months. Bone results were found to be excellent in 16 out of 30 patients (53.33%), good in 8 patients (26.66%) and fair in 4 patients (13.33%). Poor results were found in two patients. Conclusion: The study concluded that this method is an effective treatment for the management of infected non-union.